Development and optimization of a multiplex lateral flow immunoassay for the simultaneous determination of three mycotoxins in corn, rice and peanut. (15th December 2016) - Chen, Yiqiang; Chen, Qian; Han, Miaomiao; Zhou, Jinyu; Gong, Lu; Niu, Yiming; Zhang, Yuan; He, Lidong; Zhang, Liying
Highlights: A multiplex lateral flow immunoassay was developed for the determination of three mycotoxins. The preparation of antibody-gold nanoparticle conjugate was optimized. The detection limits were far below the regulatory limits set by the European Union. The assay procedure can be completed within 15 min. Abstract: A multiplex lateral flow immunoassay (LFA) is developed for the simultaneous on-site determination of three mycotoxins (aflatoxin B1, zearalenone and ochratoxin A) in corn, rice and peanut. By systematically optimizing the preparation of antibody-gold nanoparticle conjugates, the size of gold nanoparticle and the position of capture antigen, the developed LFA can obtain a visual detection limit of 10 μg/kg for aflatoxin B1, 50 μg/kg for zearalenone and 15 μg/kg for ochratoxin A. For quantitative analysis, the limits of detection were 0.10–0.13 μg/kg for aflatoxin B1, 0.42–0.46 μg/kg for zearalenone, and 0.19–0.24 μg/kg for ochratoxin A, which were far below the regulatory limits set by the European Commission. At the spiked concentrations of 0.5–10.0 μg/kg, the mean recoveries of the three mycotoxins ranged from 86.2 to 114.5% with coefficients of variation less than 16.7%. These results demonstrated that the developed immunoassay can be used for routine monitoring of mycotoxin contamination.